PENGARUH VARIASI UKURAN PARTIKEL BATANG JAGUNG TERHADAP KONDUKTIVITAS TERMAL DAN PEREDAMAN SUARA KOMPOSIT PARTIKEL BATANG JAGUNG - Hafiz Gunawan Pasaribu; Amri Hidayat; Fadhli Dzil Ikram; Wirya Sarwana (Program Studi Teknik Mesin Fakultas Rekayasa Sistem Universitas Teknologi Sumbawa, 2023)
Nowadays, with the advancement of technology, it is possible that new problems arise, especially in the global environmental field. Some of these problems include global warming, noise or sound pollution, and water absorption issues. Global warming is a growing concern experienced and felt by people worldwide, characterized by increasing temperatures and unpredictable weather conditions. Reflecting on these issues, there is a need for a solution to address them. The wise solution is the production of natural-based composites. A composite is a material produced from two or more different substances that have distinct properties, resulting in a new and improved material. One natural material that can be used is corn stalks. The composition of corn cob particles used is 35, 18, and 12 mesh. Research results show that Fraction A (35 mesh) has an average thermal conductivity of 0.1976 W/mK, Fraction B (18 mesh) 0.1911 W/mK, and Fraction C (12 mesh) 1893 W/mK. In sound absorption testing, the highest sound absorption coefficient is found in Fraction A (35 mesh) at 0.352 at a frequency of 1400 Hz, while the lowest sound absorption coefficient is found in Fraction C (12 mesh) at 0.100 at a frequency of 800 Hz. In water absorption testing, Fraction A (35 mesh) has an average absorption rate of 8.56%, Fraction B (18 mesh) 10.67%, and Fraction C (12 mesh) an average of 10.97%.